New treatments for old diseases: a proposal for international collaboration and funding of oral health clinical trials - Bruce L. Pihlstrom (Blackwell Synergy, 2008)
Oral lichen planus (OLP) is a relatively rare, chronic oral disease of unknown etiology that affects the oral mucous membranes and gingiva. Its erosive form can have a major impact on quality life due to the severe pain and burning sensation that often accompanies this disease. Because the cause of this disease is obscure, treatment is varied and symptomatic including topical and systemic corticosteroids, immunosuppressive drugs, antimycotic agents, antimicrobial mouthrinses, and topical anesthetics (Ismail et al. 2007). Although some patients obtain symptomatic relief, a systematic review concluded that there is only circumstantial evidence for the superiority of various interventions over placebo for the palliation of symptomatic OLP (Zakrzewska et al. 2005).